2017
DOI: 10.1515/jpem-2016-0327
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric differentiated thyroid carcinoma: trends in practice and outcomes over 40 years at a single tertiary care institution

Abstract: Increased use of US and FNA has affected initial surgical management in the latter part of the study, possibly due to extension of adult DTC guidelines. The effects of the new pediatric DTC guidelines need further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Rubinstein et al suggested that an aggressive surgical approach may simultaneously decrease the risk of recurrence and improve prognosis in patients with more advanced or aggressive disease ( 94 ). Olmsted et al showed no difference in recurrence-free survival among patients treated with LND compared to limited node excision of no LND ( 95 ). However, location of LND was not specified.…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 99%
“…Rubinstein et al suggested that an aggressive surgical approach may simultaneously decrease the risk of recurrence and improve prognosis in patients with more advanced or aggressive disease ( 94 ). Olmsted et al showed no difference in recurrence-free survival among patients treated with LND compared to limited node excision of no LND ( 95 ). However, location of LND was not specified.…”
Section: [C] Thyroid Carcinoma Management Guidelinementioning
confidence: 99%